A case study on nxm job shop scheduling problem using heuristic approach - Yuen Poovarawan; Sharif, M. N.; Pakorn Adulbhan; Techapun Raengkhum; Kasetsart University (Bangkok : Asian Institute of Technology, 1976)
This study describes a heuristic algorithm for seeking a quick and near optimal solution to the n jobs m machines job shop scheduling problem in which each job 4as a number of operations to be performed on the specified machines in an ordering which are not the same for all jobs. The model can handle different machines required sequences including l oops, job precedence structure and start- stop lag. The objective is to minimize the total operation time. The developed heuristic algorithm is an extensions of the heuristic rules of the jobs two machines scheduling problem. At any instant during the n operation the m machines problem can be converted into a two machine problem. One of this is the machine under consideration and the other machine represents the rest of the machines required by the job through the first one. In this study, the model has been applied to solve a real-world problem. The results are observed to be sat is factory.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1976
Keywords: Scheduling (Management)